Does Management Efficiency have any Influence on Job Satisfaction? - Badriyah, Nurul; Muhtarom, Abid; DJ, Yunni Rusmawati; Titin, Titin; Rochmatullah, Mahameru Rosy; Farid, Chabib Hasan Imam Al; Mustoffa, Ardyan Firdausi (Universitas Muhammadiyah Ponorogo, 2024)
Recently, there has been a growing global need for washing services worldwide. This surge has significantly influenced the growth of washing enterprises in all nations, including Indonesia. Nevertheless, this nation's expansion of the laundry sector has led to fierce rivalry. Many laundry businesses have failed to compete because they could not effectively implement efficient human resource management. This study aims to analyze the impact of efficiency management on employee satisfaction by identifying remedies to maintain the sustainability of the laundry sector. This study primarily examines the management of human resource efficiency, emphasizing four dimensions: leadership style, work environment, rewards, and work motivation. This study examines the role of employee performance accomplishment as a mediator. This study uses structural equation modeling (SEM) approaches to quantitatively test data from 135 respondents. The results of this study suggest that the leadership style, work environment, and rewards that align with employee preferences have a substantial impact on employee job satisfaction. It means that efficient human resource management that emphasizes these three dimensions is critical to the success of laundry businesses facing intense competition. Theoretically, this study has successfully addressed the gap in previous studies. Practically, this study can provide valuable information to practitioners in enhancing the competitive edge of their laundry business.